EFEKTIVITAS PENERAPAN PIDANA MATI TERHADAP TINDAK PIDANA NARKOTIKA DI INDONESIA - HAPSARI, IFAHDA PRATAMA (Jurnal Justiciabelen, 2019)
The granting of severe penalties for the perpetrators of narcotics crimes is very appropriate to stem and reward the perpetrators of narcotics crimes in accordance with the rules set by the State through existing laws, even with the most severe penalties, namely the Criminal Penalty. differing views on the execution of the death penalty, especially for perpetrators of drug offenses caused by multi-interpretation regulations. In addition, factors outside the law, such as community saturation of drug crimes that are not subject to strict punishment, religious background of society, and social conditions of society are other aspects that greatly affect the community and law enforcers differently in seeing the death penalty for perpetrators drug crimes in Indonesia. In formulating regulations, a punishment tool should include two things, namely: First, must accommodate the aspirations of the people who demand revenge as a balance on the basis of the wrongdoing of the perpetrator. Second, it must include the purpose of punishment in the form of maintaining community solidarity, punishment must be directed at maintaining and maintaining community unity. In this context, when the Indonesian people want the application of the death penalty for drug offenders, their will cannot be banned.